Organic Glass-Forming Liquids and the Concept of Fragility - Alba-Simionesco, Christiane (Comptes Rendus. Physique)
An important category of glass-forming materials is organic; it includes molecular liquids, polymers, solutions, proteins that can be vitrified by cooling the liquid under standard conditions or after special thermal treatments. The range of applications is large from materials to life sciences and recently to electronics. To distinguish them from other systems described in this issue, some specific properties such as the range of their glass transition temperature ($T_g$), their ability to vitrify and some rules of thumb to locate $T_g$ are presented. The most remarkable property of these liquids is how fast in temperature their viscosity or structural relaxation time increases as approaching $T_g$. To characterize this behavior and rank the liquids of different strength, C.A. Angell introduced the concept of Fragility nearly $40$ years ago. He proposed to classify liquids as fragile or strong in an Arrhenius plot with $T_g$ scaling (the strongest ones have never being observed in organic glasses, except for water under specific conditions). The $T_g$ value and the fragility index of a given liquid can be changed by applying pressure, i.e. changing the density. One can then explore the properties of the supercooled/overcompressed liquid and the glass in a $P-T$ phase diagram. The $T_g$ line corresponds to an isochronic line, i.e. a line at constant relaxation time for different pairs of density-temperature. We observe that all data can be placed on master-curves that depend only on a single density- and species-dependent and T-independent effective interaction energy, $E_{∞ }(ρ )$. An isochoric fragility index is defined as an intrinsic property of a given liquid, that can help in rationalizing all the correlations between the glass properties below $T_g$ and the viscous slowing down just above $T_g$ from which they are made. Geometrical confinement of liquids is also a way to modify the dynamics of a liquid and the properties of a glass; it corresponds to a large number of situations encountered in nature. Another phase diagram $T-d$ (d defining pore size) can be defined with a non-trivial pore size dependence of the glass transition, which is also strongly affected by surface interactions.